Computer aided learning for chinese phonetics / Tan Jih Haur - Tan, Jih Haur (2002)
Computer aided learning have been implemented by lot of institutions and universities nowadays, due to the fast growing of information technology and the trends of moving towards paperles environment. Computer aided learning for chinese phonetics is a learning package to assist students in the study of chinese phonetics. This package will provide the basic pronounce of pinyin, which is a romanize system use in chinese phonetics and syllabus teaching in primary school. It also contains exercises, quizzes and games to help users make use what their learned. Besides, as a different between learning packages in the market, I also included chinese ancient scripture and poem as an additional syllabus to help user learn Chinese Phonetics from different sources. This package will be implemented in 2 languages, english and chinese. And for the chinese version, there will have simplified chinese and traditional chinese version to choose by the user. The development of this package is assisted by multimedia tool t make it a more attractive, efficient and effective during learning process. It is hope that development this package will assist all students to learn chinese phonetic with interest.